ANALYSIS OF STUDENTS' ATTITUDES TOWARDS STEM AND 21ST CENTURY SKILLS IN ELEMENTARY SCHOOL FROM A GENDER PERSPECTIVE - Wulandari, Fitria; Putri, Devi Iffadah Rizky Ariza (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Science, Technology/Engineering, Mathematics (STEM) and 21st Century Skills are crucial to be implemented for all students starting from an early age, specifically at the elementary school level. This study aims to describe students' attitudes towards STEM and 21st Century Skills in terms of gender at the elementary school level. This research is a quantitative survey using a Cross-Sectional approach, which can explain and compare the results of questionnaires given to students. Student attitudes are explained based on STEM domains and 21st Century Skills, considering gender. The research respondents were 37 elementary school students at SD Muhammadiyah 2 Sidoarjo. The results of this study show that in the Science domain, the average score of students is 3.45 (medium), in the Mathematics domain, the average score is 2.97 (low), in the Technology/Engineering domain, the average score is 3.76 (medium), and in the 21st Century Skills domain, the average score is 3.91 (medium). Additionally, there is a significant difference between the attitudes of male and female students towards STEM and 21st Century Skills.